Actual usage conditions, energy savings and associated emission reductions of washing machines - Saidur, Rahman; Masjuki, Haji Hassan; Jamaluddin, M.Y.; Yap, F.C. (Transactions Hong Kong Institution of Engineers, 2006)
About 19 of the total electricity production is consumed in the residential sector and this fraction is expected to grow in future. Air conditioners, refrigerators, washing machines and other appliances are major energy users in this sector. In this paper, the energy consumption of 50 real-houses domestic clothes washers have been monitored to give an overview of the usage pattern of this appliance in Malaysian households. A questionnaire was designed to get relevant information regarding the usage of this appliance in the actual environment as well. This information is paramount in shaping or implementing a program that would get more support from users. Finally, energy savings, bill savings and CO 2 reductions associated with energy savings have been calculated and presented in this paper for using horizontal axis machines rather than vertical axis using actual monitored data.